Unsaturated Fatty Acid Synthesis in the Gastric Pathogen Helicobacter pylori Proceeds via a Backtracking Mechanism. Issue 12 (22nd December 2016) - Bi, Hongkai; Zhu, Lei; Jia, Jia; Zeng, Liping; Cronan, John E.
Summary: Helicobacter pylori is a Gram-negative bacterium that inhabits the upper gastrointestinal tract in humans, and the presence of this pathogen in the gut microbiome increases the risk of peptic ulcers and stomach cancer. H. pylori depends on unsaturated fatty acid (UFA) biosynthesis for maintaining membrane structure and function. Although some of the H. pylori enzymes involved in UFA biosynthesis are functionally homologous with the enzymes found in Escherichia coli, we show here that an enzyme HP0773, now annotated as FabX, uses an unprecedented backtracking mechanism to not only dehydrogenate decanoyl-acyl carrier protein (ACP) in a reaction that parallels that of acyl-CoA dehydrogenase, the first enzyme of the fatty acid β-oxidation cycle, but also isomerizes trans -2-decenoyl-ACP to cis -3-decenoyl-ACP, the key UFA synthetic intermediate. Thus, FabX reverses the normal fatty acid synthesis cycle in H. pylori at the C10 stage. Overall, this unusual FabX activity may offer a broader explanation for how many bacteria that lack the canonical pathway enzymes produce UFA-containing phospholipids. Highlights: UFA biosynthesis is required to maintain membrane function in bacteria Many bacteria lack the canonical unsaturated fatty acid UFA synthetic pathway An enzyme that inserts a double bond into a fully saturated acyl chain is reported The enzyme has both dehydrogenase and isomerase activities Abstract : Bi et al. report a flavin enzyme that reverses the normal fatty acid synthetic pathway to introduce a cis double bond into a saturated acyl chain. The enzyme has both dehydrogenation and isomerase activities. This enzyme allows unsaturated fatty acid synthesis by a non-canonical pathway.